Current Situation and Innovative Methods of Brass Music Teaching Based on Network Information Technology - Liu, Li (Journal of Electrical Systems, 2024)
- The intersection of education and technology has witnessed a significant transformation in recent years, with a particular focus on optimizing remote learning experiences. Maintaining network resources for brass music education is crucial to ensure a seamless and effective learning experience. Hence, this paper proposed SDNcOIT (Software-Defined Networking cloud Optimal Information Technology) model in the context of brass music education, a discipline that demands real-time audio and video interactions. The proposed SDNcOIT model uses the cloud environment integrated SDN architecture for the evaluation of brass music education. The constructed network comprises Software-Defined Networking, cloud technology, and a rule-based model, the SDNcOIT system presents a compelling case for enhancing the delivery of music education to students worldwide. The SDNcOIT model implemented the optimization model within the SDN environment for the analysis of the evaluation of the user experience in the cloud environment. The proposed SDNcOIT model uses the gradient descent optimization model for the computation of the brass music in the cloud environment. Through the implementation of the optimization process within the SDNcOIT the features are optimized in the cloud with SDN architecture for the analysis of user experience. The findings 6om this study reveal substantial performance improvements over time, exemplified by reduced latency, increased throughput, minimized packet loss, and elevated user satisfaction. These improvements are pivotal for a discipline where the quality of audio and video content is paramount. The scalability of the cloud infrastructure ensures that the system can accommodate varying dataset sizes, adapthig seamlessly to the dynamic requirements of a growing brass music program. Furthermore, the rule-based model's growing adherence to network behavior results hi an exceptionally efficient and well-optimized network, aligning harmoniously with the educational objectives of brass music instruction.